Higher Adolescent Body Mass Index Is Associated with Lower Regional Gray and White Matter Volumes and Lower Levels of Positive Emotionality - Kennedy, James T.; Collins, Paul F.; Luciana, Monica (Frontiers in Neuroscience, 2016)
Adolescent obesity is associated with an increased chance of developing serious health risks later in life. Identifying the neurobiological and personality factors related to increases in adiposity is important to understanding what drives maladaptive consummatory and exercise behaviors that result in obesity. Previous research has largely focused on adults with few findings published on interactions among adiposity, brain structure, and personality. In this study, Voxel Based Morphometry (VBM) was used to identify associations between gray and white matter volumes and increasing adiposity, as measured by Body Mass Index percentile (BMI%), in 137 adolescents (age range: 9–20 years, BMI% range: 5.16–99.56). Variations in gray and white matter volume and BMI% were then linked to individual differences in personality measures from the Multidimensional Personality Questionnaire (MPQ). After controlling for age and other covariates, BMI% correlated negatively with gray matter volume in the bilateral caudate (right: partial r = −0.338, left: r = −0.404), medial prefrontal cortex (partial r = −0.339), anterior cingulate (partial r = −0.312), bilateral frontal pole (right: partial r = −0.368, left: r = −0.316), and uncus (partial r = −0.475) as well as white matter volume bilaterally in the anterior limb of the internal capsule (right: partial r = −0.34, left: r = −0.386), extending to the left middle frontal subgyral white matter. Agentic Positive Emotionality (PEM-AG) was correlated negatively with BMI% (partial r = −0.384). PEM-AG was correlated positively with gray matter volume in the right uncus (partial r = 0.329). These results suggest that higher levels of adiposity in adolescents are associated with lower trait levels in reward-related personality domains, as well as structural variations in brain regions associated with reward processing, control, and sensory integration.